Transformational Leadership dan Organizational Commitment Terhadap Productivity yang di Pengaruhi Oleh Knowledge Sharing - M. Iqbal Baharuddin (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to examine the influence of Transformational Leadership and Organizational Commitment on Productivity, with Knowledge Sharing acting as a mediating variable. A quantitative research approach was employed. The study population consisted of manufacturing company operators meeting specific criteria, with a sample size of 75 respondents. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicate that Transformational Leadership, Organizational Commitment, and Knowledge Sharing all have a significant positive effect on Productivity. Furthermore, Transformational Leadership and Organizational Commitment were found to have a significant positive effect on Knowledge Sharing. Knowledge Sharing was shown to mediate the relationship of Transformational Leadership and Organizational Commitment with Productivity. These findings demonstrate that Transformational Leadership and Organizational Commitment are crucial factors influencing Productivity, both directly and through Knowledge Sharing as a mediating variable. Consequently, the findings suggest that efforts to enhance Knowledge Sharing and employee commitment to the organization constitute effective strategies for boosting Productivity within the company.